1999
DOI: 10.2337/diabetes.48.1.198
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces systemic methylglyoxal levels in type 2 diabetes.

Abstract: Methylglyoxal (MG) is a reactive alpha-dicarbonyl that is thought to contribute to diabetic complications either as a direct toxin or as a precursor for advanced glycation end products. It is produced primarily from triose phosphates and is detoxified to D-lactate (DL) by the glyoxalase pathway. Because guanidino compounds can block dicarbonyl groups, we have investigated the effects of the diamino biguanide compound metformin and of hyperglycemia on MG and its detoxification products in type 2 diabetes. MG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
269
2
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(297 citation statements)
references
References 14 publications
12
269
2
14
Order By: Relevance
“…Radioactivity was determined with a well counter. The specific activities of 111 In-BSA, 111 In-GA-BSA, and 111 In-MG-BSA were 12×10 6 , 11×10 6 and 11×10 6 cpm/mg protein, respectively.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Radioactivity was determined with a well counter. The specific activities of 111 In-BSA, 111 In-GA-BSA, and 111 In-MG-BSA were 12×10 6 , 11×10 6 and 11×10 6 cpm/mg protein, respectively.…”
Section: Methodsmentioning
confidence: 94%
“…Recent studies reported that several aldehydes such as glycolaldehyde (GA), glyoxal, methylglyoxal (MG), and 3-deoxyglucosone are generated during the Maillard reaction from glucose, a Schiff base, or Amadori products [3,4]. A much stronger chemical reactivity than that of glucose indicates the important role of these aldehydes in the in vivo generation of AGE structures [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has reported a 40-50% reduction in coronary events with metformin treatment, though glycaemic control was not as effective as intensive treatment with sulphonylureas or insulin [35]. The increased methylglyoxal concentrations detected in people with diabetes is significantly reduced by metformin [36], perhaps due to carbonyl trapping reactions [31,37]. Hydralazine has been employed clinically as an antihypertensive agent, but is known to react with carbonyls [38,39]; this is consistent with a potential protective effect against glycation [25].…”
Section: Discussionmentioning
confidence: 99%
“…These studies put focus on the mechanisms by which metformin lowers the risks of microvascular and macrovascular disease such as lowering weight gain and hyperinsulinemia, enhancing the function of endothelial function, and fibrinolysis, and reduction of low grade inflammation, oxidative stress, and glycation [12][13][14] . Other studies showed that other benefits of metformin treatment through enhance glycemic control and to lower insulin needs and weight gain [16][17][18] .…”
Section: Characteristics Of Study Participantsmentioning
confidence: 99%
“…Several studies have indicated to the mechanisms by which metformin lowers the risks of microvascular and macrovascular disease including reduced weight gain and hyperinsulinemia, enhancing the function of endothelial function, and fibrinolysis, and reduction of lowgrade inflammation, oxidative stress, and glycation [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%